Personalisation in social work - Gardner, Ali, author. 4 0 16; 5 (London : Learning Matters, an imprint of SAGE Publications Limited, 2014)
The government agenda on Personalisation and self-directed support is fast-moving and rapidly changing. It is vital therefore that students and practitioners alike are aware of the key issues and debates, as well as the policy that surrounds this area of practice. This timely and fully revised second edition provides an overview of the personalisation agenda and looks at the recent legislation in a broad historical and theoretical perspective. This approach will provide opportunities for students to consider the changes to the social work role and to evaluate the impact of this for service users and as practitioners.
Personalisation -- where did it come from? / Ali Gardner -- Personalisation -- a value base for practice / Ali Gardner -- Personalisation in practice / David Gaylard -- Service user groups and personalisation / Ali Gardner -- Service user narrative / Ali Gardner -- Safeguarding and personalisation / David Gaylard -- Preparing for practice and the professional capabilities framework / Ali Gardner -- Personalisation -- a newly qualified perspective / Natalie Robinson -- Conclusion -- Appendixes: 1. Professional capabilities framework -- 2. Subject benchmark for social work.
Previous edition: 2011.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Community-based social services;Patient participation -- Great Britain.; Great Britain; 20; 2